2019
DOI: 10.1155/2019/5036160
|View full text |Cite
|
Sign up to set email alerts
|

Jackhammer Esophagus: From Manometric Diagnosis to Clinical Presentation

Abstract: Background. Jackhammer esophagus is a hypercontractile esophageal disorder recently brought to light with the advent of high resolution manometry (HRM). As little is known about its clinical presentation, the aim of this study was to identify the clinical characteristics associated with this new gastrointestinal motility disorder. Methods. A retrospective study was conducted on patients visiting the CHUM’s Gastro-Intestinal Motility Center from January 2015 to December 2017. The HRM diagnoses were collated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 11 publications
4
44
0
7
Order By: Relevance
“…Diagnoses of JE comprised 1.97% [95% CI: 1.39%-2.78%; Cochran's Q = 81.7, I 2 = 87.8%] of HRM studies based on eleven studies reporting this data in unselected symptomatic individuals referred for HRM [16][17][18][19][20][21][22][23][24][25][26] ( Figure 2). On sensitivity analysis, we found that Zuluaga…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnoses of JE comprised 1.97% [95% CI: 1.39%-2.78%; Cochran's Q = 81.7, I 2 = 87.8%] of HRM studies based on eleven studies reporting this data in unselected symptomatic individuals referred for HRM [16][17][18][19][20][21][22][23][24][25][26] ( Figure 2). On sensitivity analysis, we found that Zuluaga…”
Section: Demographicsmentioning
confidence: 99%
“…The mean pooled age of patients diagnosed with JE was 60.8 years [95% CI: 57.1-64.4; Cochran's Q = 51.2, I 2 = 84.4%], 16,20-22,25,27-30 and 64.9% of diagnosed patients were female [95% CI: 57.7%-72.1%; Cochran's Q = 42.6, I 2 = 71.8%] 16,[20][21][22][23]25,26,[28][29][30][31][32][33]. …”
mentioning
confidence: 99%
“…Enough solution (1 mL) was applied to cover the catheter tip. The catheter was then inserted intranasally, and the tests were conducted in standard fashion as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Patients who underwent EM or apH from January 2017 to June 2018 had a 2% viscous lidocaine hydrochloride solution (Odan Laboratories) applied intranasally (1 mL) by syringe a few (3)(4)(5) minutes before their test. The same solution was also applied to the catheter as both lubrication and as a topical anesthetic.…”
Section: Prospective Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation